Behaviour of precast concrete beam–column sub-assemblages subject to column removal - Kang, Shao-Bo; Tan, Kang Hai (Engineering structures, 2015)
•Precast concrete beam–column sub-assemblages were able to develop compressive arch action and catenary action under column removal scenarios.•Increasing the reinforcement ratio increased the resistance of sub-assemblage.•Flexural deformations of the beam significantly contributed to the deformation capacity of sub-assemblages.•Horizontal shear cracking was observed cross the interface between the precast beam unit and cast-in-situ concrete topping. Under column removal scenarios, initiation of alternate load paths via adjacent bridging beams to redistribute vertical loads requires certain level of ductility and continuity in beam–column joints. Although this approach does not consider the magnitude of the blast event, it is threat-independent and offers a minimum level of robustness against column removal scenarios. This paper studies the behaviour of precast concrete sub-assemblages which comprised two precast beams and a precast column joining together by cast-in-place concrete topping above the two beams and the beam–column joint. The top longitudinal reinforcement in the structural topping of precast beams passed through the beam–column joint continuously. However, the bottom beam longitudinal reinforcement was either lap-spliced or anchored as a 90° bend within the cast-in-place joint. Due to discontinuity of bottom beam longitudinal reinforcement, the ability of such an assemblage to develop compressive arch action (CAA) and subsequent catenary action has to be investigated, in particular, the effect of the top and bottom beam longitudinal reinforcement ratios. Test results show that significant CAA and catenary action developed in the beams under column removal scenarios, with pull-out failure of the bottom beam reinforcement in the joint. The enhancement of CAA and catenary action to structural resistance greatly depends on joint detailing and beam reinforcement ratio. Furthermore, the effectiveness of horizontal shear transfer between concretes cast at different times is examined at large deformation stage. Finally, practical suggestions are given to enhance structural resistance of a similar type of precast concrete sub-assemblages.